Nutritional status of children in Bangladesh: Measuring Composite Index of Anthropometric Failure (CIAF) and its determinants - Rana Ejaz Ali Khan; Muhammad Ali Raza (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The objective of the current analysis is to see the factors responsible for malnutrition in children (under-5 years) in urban and rural areas of Bangladesh. In this study binary logistic model is applied to 1831 observations of urban and 3427 observations of rural areas. The Composite Index of Anthropometric Failure (CIAF) is constructed and used as an indicator of malnutrition. It is estimated that malnutrition in rural children is much higher than in urban children. The results have shown that probability of CIAF is negatively associated with birth-interval of child (in urban areas only), mother's education, wealth index of the household, mother's BMI and number of children (5-15 years) in the household (in urban areas only). However, birth-order of the child (in urban areas only), child's age (in rural areas only), breastfeeding, incidence of diarrhea and household size (in urban areas only) positively affect the probability of malnutrition in children. For the policy formulation mother's education, duration of breastfeeding and nutritional status (BMI) of the mother is recommended to eliminate malnutrition. The rural areas need special focus in the policy making.
Keywords: 330; anthropometry; rural-urban disparity; child health; child growth; household economics